2022
DOI: 10.3390/ani12151911
|View full text |Cite
|
Sign up to set email alerts
|

CYP19A1 May Influence Lambing Traits in Goats by Regulating the Biological Function of Granulosa Cells

Abstract: Abnormal expression of CYP19A1, a gene related to steroid hormone synthesis, causes steroid hormone disruption and leads to abnormal ovulation in granulosa cells. However, the exact mechanism of CYP19A1 regulation is unclear. In this study, we confirmed the localization of CYP19A1 in goat ovarian tissues using immunohistochemistry. Subsequently, we investigated the effects of CYP19A1 on granulosa cell proliferation, steroid hormone secretion, and expression of candidate genes for multiparous traits by overexpr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 47 publications
2
3
0
Order By: Relevance
“…9 ). This result was consistent with the report of Zhang et al in goat GCs [ 39 ]. In addition, Zhao et al demonstrated in a mouse model that PAK1 mediates a negative regulation of E 2 in the non-classical ERα pathway in the reproductive axis, and also confirmed that PAK1 inhibits E 2 secretion in this study, thereby inhibiting follicular development and ovulation, thereby regulating sheep reproduction [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…9 ). This result was consistent with the report of Zhang et al in goat GCs [ 39 ]. In addition, Zhao et al demonstrated in a mouse model that PAK1 mediates a negative regulation of E 2 in the non-classical ERα pathway in the reproductive axis, and also confirmed that PAK1 inhibits E 2 secretion in this study, thereby inhibiting follicular development and ovulation, thereby regulating sheep reproduction [ 40 ].…”
Section: Discussionsupporting
confidence: 94%
“…Wang et al noted that GLOD4 expression was significantly upregulated in the testis of Tibetan sheep wwith age, and GLOD4 was only expressed in leydig cells and that GLOD4 was mainly observed in the cytoplasm [23], our immunohistochemistry revealed that GLOD4 was expressed only in leydig cells, which is consistent with the findings of Wang et al However, our subcellular localization analysis revealed that GLOD4 was widely expressed in both the nucleus and the cytoplasm of leydig cells. Interestingly, in a recent study, fluorescently tagged GLOD4 protein was widely distributed in the cytoplasm and nucleus of human retinal pigment epithelial cells (hTERT-RPE1) [28], which may result from differential gene expression in different species [29][30][31].…”
Section: Discussionsupporting
confidence: 90%
“…As a goat breed that is well adapted to the highland mountain environment, Qianbei Ma goats have a long history of breeding in Guizhouwith a medium body size, rough feeding resistance, strong disease resistance, good fur quality and strong fertility. Thus, Qianbei Ma goats are a good model animal for exploring the reproductive traits of plateau goats [23]. Therefore, the aim of this study was to investigate the profile of GLOD4 gene expression in the testes of goats at different ages and to analyze the regulatory effect of the GLOD4 gene on testicular leydig cells.…”
Section: Introductionmentioning
confidence: 99%
“…It is known that CYP19A1 is widely expressed in ovaries and granulosa cells, where it converts androgens into estrogens. Importantly, CYP19A1 has been demonstrated to influence lambing traits in goats by affecting granulosa cell proliferation, hormone secretion, and the expression of candidate genes associated with traits for multiple births [10,37]. GHRHR, a member of the superfamily of the G-protein-coupled receptor subfamily, works together with the growth-hormone-releasing hormone (GHRH) to regulate the growth hormone axis and the development and proliferation of pituitary somatotropes.…”
Section: Discussionmentioning
confidence: 99%